PENERAPAN MODEL KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DENGAN ARCS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 1 KOTO XI TARUSAN KAB. PESISIR SELATAN - Wahyuni, Sari; Zulfaneti, Zulfaneti; Yunita, Alfi (STKIP PGRI Sumbar, 2014)
ABSTRACTLearning more dominated by teachers and students receive without actively thinking led to an understanding of concepts and low student activity. Learning model that utilizes the interaction of students in cooperative learning that is a model of NHT with ARCS. This study aims to determine how students understanding of concepts and activities that apply the cooperative model of NHT with ARCS. This type of research is experimental research. The population in this study was a class VII Koto XI SMPN 1 Tarusan Academic Year 2013/2014 except VII1 class. Class VII2 is a class of experimental and control class is VII3 class. This research instrument is the student activity sheet and test understanding of mathematical concepts. Data analysis techniques used t test. Based on the analysis of data known to both classes of normally distributed and homogeneous samples. Hypothesis test results obtained t = 1.85 is greater than ttable = 1.645 so H0 is rejected and accept H1. Concluded that the students understanding of mathematical concepts that apply to the model of NHT with ARCS better understanding of mathematical concepts than students who apply conventional learning in class VII Koto XI SMPN 1 Tarusan.